Development Product Inclusive Islamic Finance for Push Growth of MSMEs in Rural Areas - Chekole Gizachew Melisew; Nur Saebah (Journal of Sharia Micro Enterprise and Cooperation, 2024)
Study This aiming for develop product finance inclusive sharia​ use support growth of Micro, Small, and Medium Enterprises (MSMEs) in rural areas. MSMEs play a role important in Indonesian economy, especially in the region’s rural areas. However, access they to service finance sharia Still limited consequence low literacy finance, limitations infrastructure, and perception that cost service sharia taller compared to product conventional. Research This use method survey and interview deep towards MSMEs in several rural areas for identify need as well as obstacles faced. Research results show that the majority of MSMEs in rural areas will consider service finance sharia If product the more easily accessible and affordable. Recommendations proposed policy​ includes literacy programs finance sharia, incentives for institution finance sharia in rural areas, and development product digital based. Research This give guide practical for taker policies and institutions finance in to design product finance sharia that supports inclusion finance and improve welfare rural economy.​